Confessions of a Science Blogaholic: Highs, Lows, and Increasing Liabilities - Smith, David Roy (Frontiers in Communication, 2017)
Social media have transformed the way we talk about science. Blogging in particular has become popular among scientists of all stripes, and has proven to be a useful tool for engaging the public in scientific discourse. Science bloggers have also helped to instill change within academia, highlighting discrimination, misconduct, and gross errors in peer review. But for all the laudable activism, the thought-provoking commentaries, and the brilliant posts that make up the scientific blogosphere, there is an equal if not greater amount of scientific gobbledygook. And for scientists who choose to blog, it is getting harder and harder to attract and sustain an online audience, even for the very best science writers. Given this competitive online environment, is it even worth the effort of starting and maintaining a blog? What are the perks, if any, of becoming an online science sensation? What are the drawbacks? In this light-hearted essay, I explore these and other blog-related questions, as well as my own relationship with science blogging, as I seek to understand the current state of the scientific blogosphere.